Effect of chlorhexidine gluconate on porosity and compressive strength of a glass ionomer cement - Marti, Luana Mafra; Azevedo, Elcilaine Rizzato; Mata, Margareth Da; Giro, Elisa Maria Aparecida; Zuanon, Angela Cristina Cilense (Universidade Estadual Paulista Júlio de Mesquita Filho, 2014)
INTRODUCTION: For presenting wide antibacterial activity, chlorhexidine (CHX) has been extensively used in dentistry and can be easily incorporated into the glass ionomer cement (GIC) and consequently released into the oral cavity.AIM:The aim of this study was porosity and compression strength of a GIC, that was added to different concentrations of CHX.MATERIAL AND METHOD:Specimens were prepared with GIC (Ketac Molar Esaymix) and divided into 4 groups according to the concentration of CHX: control, 0.5% and 1% and 2% (n = 10). For analysis of pores specimens were fractured with the aid of hammer and chisel surgical, so that the fracture was performed in the center of the specimens, dividing it in half and images were obtained from a scanning electron microscope (SEM) analyzed in Image J software. The compressive strength test was conducted in a mechanical testing machine (EMIC - Equipment and Testing Systems Ltd., Joseph of the Pines, PR, Brazil). Statistical analysis was performed by ANOVA, Tukey test. Significance level of 5%.RESULT:No statistically significant changes between the study groups was observed both for the number of pores as well as for the compressive strength.CONCLUSION:The use of GIC associated with CHX gluconate 1% and 2% is the best option to be used in dental practice.

INTRODUÇÃO:Por apresentar ampla atividade antibacteriana, a clorexidina (CHX) tem sido amplamente utilizada em odontologia, podendo ser facilmente incorporada ao cimento de ionômero de vidro (CIV) e liberada consequentemente na cavidade bucal.OBJETIVO:O objetivo neste estudo foi avaliar a porosidade e resistência à compressão de um CIV, ao qual foi adicionado diferentes concentrações de CHX.MATERIAL E MÉTODO:Os espécimes foram preparados com CIV (Ketac Molar Esaymix) e divididos em 4 grupos de acordo com a concentração de CHX: controle, 0,5% e 1% e 2% (n=10). Para análise dos poros os espécimes foram fraturados com auxílio de martelo e cinzel cirúrgicos, de modo que a fratura era realizada no centro do corpo de prova, dividindo-o ao meio e as imagens obtidas no microscópio eletrônico de varredura (MEV) analisadas no software Image J. O teste de resistência à compressão foi realizado na máquina de ensaios mecânicos (EMIC - Equipamentos e Sistemas de Ensaios Ltda, São José dos Pinhais, PR, Brazil). A análise estatística foi realizada por ANOVA, complementada pelo teste de Tukey. Nível de significância adotado de 5%.RESULTADO:Não se observou alteração estatisticamente significante entre os grupos estudados tanto para o número de poros quanto para a resistência à compressão.CONCLUSÃO:O uso de CIV associado ao gluconato de CLX a 1% e 2% é a melhor opção para ser utilizada na clínica odontológica.
Efeito da adição de gluconato de clorexidina na porosidade e resistência à compressão de um cimento de ionômero de vidro
Keywords: Glass ionomer cements; chlorhexidine; porosity; Cimentos de ionômeros de vidro; clorexidina; porosidade